Pengaruh Kinerja Keuangan Terhadap Return Saham Perusahaan Sektor Multifinance - Chyntia Tiara Putri; Dwi Susilowati; Nadi Hernadi Moorcy (Universitas Sains dan Teknologi Komputer, 2025)
This study aims to test the influence of financial performance as measured by Current Ratio and Debt to Equity Ratio on stock returns. The data used are secondary data from the Annual Report. The sample used in this study was 15 Multifinance Sector companies listed on the Indonesia Stock Exchange for the period 2020-2023, so that the data observed was 60. The type of research used is descriptive and associative with a quantitative method that aims to determine the influence of independent variables on dependent variables, with SPSS analysis tool. The findings of this study indicate that the Current Ratio and Debt to Equity Ratio partially does not have a positive effect on stock returns. On the other hand, Earning per Share (EPS) has successfully influenced stock returns.